Ramayana dalam Kitab Omong Kosong karya Seno Gumira Ajidarma: Ramayana in Kitab Omong Kosong by Seno Gumira Ajidarma - Hasina Fajrin R.; Andi Indah Yulianti (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Classic literature has something distinctive, thus attract interest from writers to retell it with the reduction, addition, or creation of new story versions. This paper will discuss the Kitab Omong Kosong by Seno GumiraAjidarma by comparing Ramayana with the Kitab OmongKosong and rationalize the impact of convention and innovation which is an intertextual reading of Seno against Ramayana using intertextual theory. The results of the discussion showed that Seno GumiraAjidarma through the novel Buku Omong Kosong deconstructed the story and stated that even evil is not always evil, there is always a good side that everyone has. Kitab Omong Kosong is not only inspired by the story of Ramayana, although the story of Ramayana is dominant, but it is also the story of Sutasoma, Jataka-Mala, Siwaratrikalpa, Bubukshah and Handling Aking and Togog, even Maneka and Satya. Seno's repertoire of these stories is very adequate to produce novels that fulfill the readers' curiosity about classic literary canons. Even writers, who are new to the Ramayana story, are made to want to know more about the other classics literary canons. This is also a way for Seno to not only retell the story of Ramayana, but also introduce other stories toreaders who are more interested in reading novels than scavenging the story in classics literary books.